The effect of green policy announcements on sectoral stock returns: empirical evidence from Vietnam - Thu Hien Bui; Khanh Linh Vu (Cogent Economics & Finance)
This study examines the impact of Green Policy Announcements (GPAs) on sectoral stock returns in the Vietnamese stock market using event study methodology. Environmental sustainability has become a critical issue globally, and Vietnam is no exception. As the country experiences rapid economic growth, it faces significant environmental challenges, including increased pollution and climate change impacts. The Vietnamese government has implemented various green policies to address these challenges. Using data from 737 firms listed on the Hanoi Stock Exchange (HNX) and Ho Chi Minh Stock Exchange (HSX), the study investigates the effects of 20 GPAs issued between 2012 and 2022. Findings reveal significant sectoral impacts on returns, volatility, and trading volume, with notable sensitivity in the Construction & Materials and Real Estate sectors. These results suggest that green policies reduce investor uncertainty in these sectors, reflecting their importance in Vietnam's environmental policy landscape. Findings provide valuable insights for policymakers, managers and investors, highlighting the need for tailored approaches to support the transition to a greener economy. In addition, this study highlights significant sector-specific responses to Green Policy Announcements (GPAs) in Vietnam, emphasizing the need for tailored interventions in heavily polluting sectors like Construction & Materials and Chemicals. It underscores the importance of incentivizing green finance, enhancing regulatory transparency, and leveraging stock market responses to refine policy effectiveness.